80.8k views
1 vote
Как это решить пожалуйста помогите пожалуйста решить прямо сейчас ​

Как это решить пожалуйста помогите пожалуйста решить прямо сейчас ​-example-1
User Konchy
by
5.4k points

1 Answer

3 votes

Answer:

y = (-4)

Explanation:

Given equation is,

-2y = 4y + 24

By subtracting 4y from both the sides of the equation,

-2y - 4y = (4y + 24) - 4y

-6y = 24

By dividing the equation by (-6),


(-6y)/(-6)=(24)/(-6)

y = (-4)

User TheSystem
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.